Liquefaction of sawdust by pyrolysis - Chua, David L. (Animo Repository, 1992)
This study involves liquefaction of wood sawdust by pyrolysis at temperature 250, 300 and 350. The experimental apparatus used consists of a pyrolytic heater, condenser and reactor. Observations were made as to what the effects of temperature and size of sawdust on the rate of decomposition are. The experiments were conducted at time intervals of 30 and 60 minutes. These variations were made to determine the effects of these parameters on the liquid yield.Measurements of solid and liquid yields were made. The study showed that the liquid yield of sawdust sample increases with time and temperature also, the smaller the size of sawdust, the greater the yield would be. Therefore, to have a better yield of liquid products, the finest sawdust and the highest possible temperature are preferred.